2x-1=3/4x-7

Simple and best practice solution for 2x-1=3/4x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-1=3/4x-7 equation:



2x-1=3/4x-7
We move all terms to the left:
2x-1-(3/4x-7)=0
Domain of the equation: 4x-7)!=0
x∈R
We get rid of parentheses
2x-3/4x+7-1=0
We multiply all the terms by the denominator
2x*4x+7*4x-1*4x-3=0
Wy multiply elements
8x^2+28x-4x-3=0
We add all the numbers together, and all the variables
8x^2+24x-3=0
a = 8; b = 24; c = -3;
Δ = b2-4ac
Δ = 242-4·8·(-3)
Δ = 672
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{672}=\sqrt{16*42}=\sqrt{16}*\sqrt{42}=4\sqrt{42}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(24)-4\sqrt{42}}{2*8}=\frac{-24-4\sqrt{42}}{16} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(24)+4\sqrt{42}}{2*8}=\frac{-24+4\sqrt{42}}{16} $

See similar equations:

| -17z-20=16-15z | | -5(5b+7)=7b+29 | | 2(-x+3)=-(2x-6) | | 17-11r+7=-15r-12 | | 18=10x-3(5x-7)+8x | | .25x=50+.15x | | -7t=17-8t | | 6.7x=5.2x+12.3=12.9 | | 2x+4(x−2)=40 | | 5-3x+2(4x-3)=14 | | -10-u=4u+10 | | b/3-16=-14 | | -2(5x+10)=-80 | | −4+w+17−2/3w=16 | | 2(x-3)-x-4=15 | | -5-8w=2w+5 | | 3p+8-5p=20 | | 6w-8=5w-9 | | 43+5(d−4)= | | 7x-1=x-8 | | 8=7e | | (x+6)^3=-27 | | -4c+12+11c=-37 | | 2x-5(x-3)=2(x-10) | | x-1/7=4 | | -22+-11x=98 | | 8q+3=9q | | 17.99+76m=179.11 | | 50+6x=30+9x | | -8-5n=63 | | -m-4=-6 | | 1+8y+9=9y+2 |

Equations solver categories